2022
DOI: 10.1101/2022.07.18.499817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Somatostatin peptide signaling dampens cortical circuits and promotes exploratory behavior

Abstract: BackgroundSomatostatin (SST) neurons in the prelimbic (PL) cortex mediate a variety of behavioral states, ranging from alcohol consumption to fear learning and avoidance-related behaviors. However, little is known about the role of somatostatin peptide signaling itself to cortical functioning and behavior. Here, we sought to characterize the unique physiological and behavioral roles of the SST peptide in the PL cortex.MethodsWe employed a combination of ex vivo electrophysiology, in vivo calcium monitoring, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Studies assessing changes in anxiety-like behavior following adolescent alcohol have found mixed results, with some showing increases in anxiety-like behavior after adolescent drinking (Lee et al, 2017; Varlinskaya et al, 2020) and others showing no change (Amodeo et al, 2018). While the current study did not explore the behavioral ramifications of long-term SST excitability, the literature has long suggested a broad role for these neurons in fear learning (Cummings and Clem, 2020), threat response (Joffe et al, 2022), and alcohol use itself (Dao et al, 2021), and we have recently shown their active engagement during exploratory behaviors (Brockway et al, 2022, preprint). Therefore, the consequences of a lifelong increase in SST function may be catastrophic to the individual brain.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies assessing changes in anxiety-like behavior following adolescent alcohol have found mixed results, with some showing increases in anxiety-like behavior after adolescent drinking (Lee et al, 2017; Varlinskaya et al, 2020) and others showing no change (Amodeo et al, 2018). While the current study did not explore the behavioral ramifications of long-term SST excitability, the literature has long suggested a broad role for these neurons in fear learning (Cummings and Clem, 2020), threat response (Joffe et al, 2022), and alcohol use itself (Dao et al, 2021), and we have recently shown their active engagement during exploratory behaviors (Brockway et al, 2022, preprint). Therefore, the consequences of a lifelong increase in SST function may be catastrophic to the individual brain.…”
Section: Discussionmentioning
confidence: 94%
“…Although limited work has assessed changes in SST peptide release or expression in substance use disorders, SST represents a potential therapeutic target for a variety of neuropsychiatric illnesses (Brockway and Crowley, 2020). Future experiments should investigate changes in SST peptide release throughout development and following alcohol exposure using both optogenetic techniques (Dao et al, 2019), in vivo recording (Brockway et al, 2022, preprint), and novel biosensors (Wang et al, 2022, preprint; Xiong et al, 2021, preprint).…”
Section: Discussionmentioning
confidence: 99%